Perubahan Model Mental Siswa pada Materi Alat Optik melalui Experiential Learning - Novi Arianti; Lia Yuliati; Sunaryono Sunaryono (Pascasarjana Universitas Negeri Malang, 2018)
Abstract: The central goal of this research was to characterize the mental models of optical instruments expressed by students. The subject of this study were 35 students of class XI in SMA Negeri 1 Badegan. Mixed method embedded experimental model was conducted to probe the participant's model mental. Data obtained through interviews and tests. The results reveal that the participants held five categories of mental models of optical instrument. The development of student's model mental indicated by nearly half held a scientifically compatible model mental during and after studying Physics with Experiential Learning. Abstrak: Tujuan penelitian ini adalah untuk mengetahui model mental siswa SMA pada materi alat optik. Subjek penelitian adalah 35 siswa kelas XI SMA Negeri 1 Badegan. Penelitian menggunakan metode Mixed method embedded experimental model. Data diperoleh melalui tes dan wawancara. Hasil penelitian menunjukkan terdapat lima kategori model mental. Perubahan model mental siswa ditunjukkan dengan hampir setengah siswa di dalam kelas memiliki model mental yang sesuai dengan saintifik selama dan setelah pembelajaran Experiential Learning dilakukan.